2010
DOI: 10.1002/app.31638
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the structure at the micrometer and nanometer scales on the light transmission of isotactic polypropylene

Abstract: The spherulitic superstructure, crystallinity, and structure and morphology of crystals of isotactic polypropylene were controlled by the conditions of melt crystallization and related to the transmittance of visible light. Spherulitic samples, which contained monoclinic lamellae, were prepared by slow cooling of the quiescent melt at rates lower than 10 K/s and by isothermal melt crystallization at temperatures between 373 and 413 K. Nonspherulitic specimens, which contained nonlamellar mesomorphic domains, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…Spherulitic samples of identical crystallinity, in contrast, are rather opaque and the light transmission is about only 50%. The reasons for the different optical behavior of spherulitic and non-spherulitic samples have been described in detail in a separate study [34].…”
Section: Impact Of Crystallization Of Ipp Via the Mesophasementioning
confidence: 98%
“…Spherulitic samples of identical crystallinity, in contrast, are rather opaque and the light transmission is about only 50%. The reasons for the different optical behavior of spherulitic and non-spherulitic samples have been described in detail in a separate study [34].…”
Section: Impact Of Crystallization Of Ipp Via the Mesophasementioning
confidence: 98%
“…The mesophase domains can then be reorganized to crystals by heating, with the shape and non-spherulitic superstructure preserved. As such, it is possible to obtain semicrystalline iPP of qualitatively different crystal morphology and superstructure, which, naturally, exhibit different property profiles [28][29][30]. Similar study of the effect of variation of the pathway of solidification of the melt of PA 6 on the morphology of the ordered phase and its superstructure is not available and therefore object of this work.…”
Section: Introductionmentioning
confidence: 96%
“…It is seen that EPR15/EPR9(5/5) blend shows bigger spherulites than those of EPR9. It has been reported that the transparency of a semi‐crystalline polymer is mainly influenced by the size of the spherulite . The bigger spherulites result in strong light scattering and poor transparency .…”
Section: Resultsmentioning
confidence: 99%